Small hydrogen storage tank filled with 2LiBH4MgH2 nanoconfined in activated carbon: Reaction mechanisms and performances. (23rd April 2019) - Dansirima, Palmarin; Thiangviriya, Sophida; Plerdsranoy, Praphatorn; Utke, Oliver; Utke, Rapee
Abstract: De/rehydrogenation performances and reaction pathways of nanoconfined 2LiBH4 MgH2 into activated carbon (AC) packed in small hydrogen storage tank are proposed for the first time. Total and material storage capacities upon five hydrogen release and uptake cycles are 3.56–4.55 and 2.03–3.28 wt % H2, respectively. Inferior hydrogen content to theoretical capacity (material capacity of 5.7 wt % H2 ) is due to partial dehydrogenation during sample preparation and incomplete decomposition of LiBH4 as well as the formation of thermally stable Li2 B12 H12 upon cycling. Two-step dehydrogenation of MgH2 and LiBH4 to produce Mg and MgB2 +LiH, respectively is found at all positions in the tank. For rehydrogenation, reversibility of MgH2 and LiBH4 proceeds via different reaction mechanisms. Although isothermal condition (Tset  = 350 °C) and controlled pressure range (e.g., 30–40 bar H2 for hydrogenation) are applied, temperature gradient inside the tank and poor hydrogen diffusion through hydride bed, especially in the sample bulk are detected. This results in alteration of de/rehydrogenation pathways of hydrides at different positions in the tank. Thus, further development of hydrogen storage tank based 2LiBH4 MgH2 nanoconfined in AC includes the improvement of thermal conductivity of materials and temperature control system as well as hydrogen permeability. Highlights: Nanoconfined LiBH4MgH2-AC in small hydrogen storage tank reported for the first time. Tracking reaction mechanisms at different positions in the tank upon cycling. Investigation of phase compositions in the tank before and after H2 exchange reaction. Up to 58% of theoretical hydrogen capacity obtained from the tank.